Valve Abnormalities, Risk Factors for Heart Valve Disease and Valve Replacement Surgery in Spondyloarthritis. A Systematic Review of the Literature - Park, Hye-Sang; Laiz, Ana; Sanchez-Vega, Jesus; Díaz del Campo, Petra; Martín-Martínez, Maria Auxiliadora; Guerra-Rodríguez, Mercedes; Corominas, Hector (Frontiers in Cardiovascular Medicine, 2021)
Objective: Evaluate the evidence on the abnormalities of the aortic root and heart valves, risk and prognostic factors for heart valve disease and valve replacement surgery in spondyloarthritis. Methods: A systematic literature review was performed using Medline, EMBASE and Cochrane databases until December 2020. Prevalence, incidence, risk and prognostic factors for heart valve disease; dimension, morphology and pathological abnormalities of the valves were analyzed. Patient characteristics (younger age, history of cardiac disease or longer disease duration) and period of realization were considered for the analysis. The SIGN Approach was used for rating the quality of the evidence of the studies. Results: In total, 37 out of 555 studies were included. Overall, the level of evidence was low. The incidence of aortic insufficiency was 2.5-3.9‰. Hazard Ratio for aortic insufficiency was 1.8-2.0. Relative risk for aortic valve replacement surgery in ankylosing spondylitis patients was 1.22-1.46. Odds ratio for aortic insufficiency was 1.07 for age and 1.05 for disease duration. Mitral valve abnormalities described were mitral valve prolapse, calcification and thickening. Aortic valve abnormalities described were calcification, thickening and an echocardiographic “subaortic bump”. Abnormalities of the aorta described were thickening of the wall and aortic root dilatation. The most common microscopic findings were scarring of the adventitia, lymphocytic infiltration and intimal proliferation. Conclusions: A higher prevalence and risk of aortic valve disease is observed in patients with ankylosing spondylitis. Studies were heterogeneous and analysis was not adjusted by potential confounders. Most studies did not define accurate outcomes and may have detected small effects as being statistically significant.